Psychometric properties of the updated EORTC module for assessing quality of life in patients with lung cancer (QLQ-LC29): an international, observational field study. Issue 5 (May 2020) - Koller, Michael; Shamieh, Omar; Hjermstad, Marianne J; Hornslien, Kjersti; Young, Teresa; Chalk, Tara; Ioannidis, Georgios; Harle, Amelie; Johnson, Colin D; Tomaszewski, Krzysztof A; Serpentini, Samantha; Pinto, Monica; et al.
Summary: Background: The European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire-Lung Cancer 13 (QLQ-LC13) assesses quality of life (QOL) in patients with lung cancer and was the first EORTC module developed for use in international clinical trials. Since its publication in 1994, major treatment advances with possible effects on QOL have occurred. These changes called for an update of the module and its international psychometric validation. We aimed to investigate the scale structure and psychometric properties of the updated lung cancer module, QLQ-LC29, in patients with lung cancer. Methods: This international, observational field study was done in 19 hospitals across 12 countries. Patients aged older than 18 years with a confirmed diagnosis of lung cancer and no other previous primary tumour, and who were mentally fit with sufficient language skills to understand and complete the questionnaire were included. Patients were asked during a hospital visit to fill in the paper versions of the core questionnaire EORTC QLQ-C30 plus QLQ-LC29, and investigators selected half of these patients to complete the questionnaire again 2–4 weeks later. Our primary aim was to assess the scale structure and psychometric properties of EORTC QLQ-LC29. We analysed scale structure using confirmatory factor analysis; reliability using Cronbach's α value (internal consistency) and intra-class coefficient (test–retest reliability); sensitivity using independent t tests stratified by Karnofsky performance status; and responsiveness to change over time by ANOVA. This study is registered with ClinicalTrials.gov, NCT02745691 . Findings: Between April 12, 2016, and Sept 26, 2018, 523 patients with a confirmed diagnosis of either non-small-cell lung cancer (n=442) or small-cell lung cancer (n=81) were recruited. Confirmatory factor analysis provided a solution composed of five multi-item scales (coughing, shortness of breath, fear of progression, hair problems, and surgery-related symptoms) plus 15 single symptom or side-effect items: χ 2 =370·233, root mean square error of approximation=0·075, and comparative-fit index=0·901. Cronbach's α for internal consistencies of all multi-item scales were above the threshold of 0·70. Intra-class coefficients for test–retest reliabilities ranged between 0·82 and 0·97. Three (shortness of breath, fear of progression, and hair problems) of the five multi-item scales showed responsiveness to change over time (p values <0·05), as did nine of 15 single symptom items. Four (coughing, shortness of breath, fear of progression, and surgery-related symptoms) of the five multi-item scales and ten of the 15 single symptom items were sensitive to known group differences (ie, lower vs higher Karnofsky performance status). Interpretation: Results determined the psychometric properties of the updated lung cancer module, which is ready for use in international clinical studies. Funding: EORTC Quality of Life Group.